Implementation of an Educational iPad Application for Patients With Chronic Hepatitis B - Ha, Phil; Hean, Rattanak; Tang, Patrick; Choy, Audrey; Thakur, Udit; Dev, Anouk (Frontiers in Public Health, 2019)
Chronic Hepatitis B (CHB) contributes to a high public health burden in Australia from chronic liver disease and hepatocellular carcinoma. Health literacy impacts on multiple aspects of long term management, including surveillance and long term follow up. We designed and implemented a multilingual educational iPad application for outpatients to use while in the clinic waiting room. The application employed an interactive and multimodal approach to education. It utilised graphics, audio and text to convey practical information regarding transmission of disease, long term complications, treatment and surveillance. Participants were recruited from a tertiary liver clinic and assigned to either standard treatment (routine clinical consult only) or the iPad group (clinical consult and additional education with the iPad app). There were 54 participants (control n=29, iPad n=25). Knowledge was assessed at baseline, secondly after the clinician appointment and finally at 6 months. Median follow up time was 6.1 months (range 0-18 months) and 87% of participants completed the final survey. At baseline, there was no difference in age, gender, proportion of newly referred patients, or use of antivirals. Baseline knowledge was similar in the two groups (61.4% vs 55.1%, p=0.33). The iPad group scored significantly higher after the first consult (79.5% vs 61.5%, p=0.0005). This improvement remained significant by the end of follow up (72.6% vs 61.0%, p=0.0472). To conclude, interactive education with iPads may be an effective way to improve patient knowledge.